'A Bad Peace?' – The 1937 Nagoya Pan-Pacific Peace Exhibition. Issue 2 (4th May 2018) - Hopson, Nathan
ABSTRACT: The March–May 1937 Nagoya Pan-Pacific Peace Exhibition (NPPPE) promoted the Nagoya region as an industrial and cultural center of the empire. Though intended to show the city prospering in free-trade, capitalist peace, it was a 'mega-event, ' large and complex enough to permit alternative interpretations, resistance, and even discord. The Imperial Japanese Army (IJA) objected to a 'peace' expo, extracting various concessions from NPPPE organizers, including a national defense hall and live-fire demonstrations. This made the event appear a cynical misappropriation of the concept of 'peace.' However, underneath this bellicose veneer is evidence that even on the eve of all-out war, local business and government elites clung to a 1920s style vision of peace through international trade and intercourse rather than through autarky and military force. Nagoya could not prevent military interference in the peace expo, but the city's commitment to an agenda diverging from those of the IJA and Tokyo testifies to the continued political diversity of Japan in the mid to late 1930s.